Quantifying the Source Term and Uniqueness of the August 12, 2017 Pacific Northwest PyroCb Event. Issue 13 (2nd July 2021) - Fromm, M. D.; Kablick, G. P.; Peterson, D. A.; Kahn, R. A.; Flower, V. J. B.; Seftor, C. J.
Abstract: A pyrocumulonimbus (pyroCb) firestorm event known as the Pacific Northwest Event (PNE), on August 12, 2017, is examined with a focus on newly reported details of the pyroconvective injections, transport pathway, and young‐plume altitude. Because PNE and a subsequent pyroCb event in Australia have been compared to classic stratospheric volcanic plumes, a prime motivation for this work was to exhaustively characterize the beginning of PNE, and to show how it compared to major stratospheric plumes from prior events. We find and report direct evidence that PNE pyroconvection involved seven discrete storms, at least two of which injected a plume to at least 13.7 km, up to 2.5 km above the local tropopause. The morning after, stratospheric smoke was observed above the tropopause to altitudes as great as 16 km. We also quantify for the first time that PNE was preceded by a pyroCb injection one day earlier, generating a plume noteworthy on its own but overwhelmed by the PNE smoke. Our comparison of PNE with five earlier pyroCb events reveals that PNE was not distinctive with respect to its injection and nascent plume height. However, it did produce the greatest known ultraviolet absorbing aerosol index and plume longevity as of 2017. Plain Language Summary: Wildfire‐generated thunderstorms, which in ways resemble explosive volcanic eruptions, can dot the landscape as an individual blowup or a cluster over a complex of fires. A technical term for these storm clouds is "pyrocumulonimbus" ("pyroCb" for short). The Pacific Northwest Event (PNE) pyroCbs in 2017 gained wide attention. Its stratospheric smoke plume was extraordinary for having ascended to a height far above its injection. It was notable also for its long stratospheric lifetime. There is growing recognition that such noteworthy pyroCb eruptions are comparable to major volcanic plumes. But pyroCb science is still evolving and there is considerable uncertainty regarding PNE in the context of other documented pyroCb and volcanic events in terms of a host of important quantifiable measures. We, therefore, undertake an effort to quantify PNE's beginning and effect, then compare it with other major pyroCbs that have been incompletely characterized in the literature. We find that PNE was unprecedented in some but not all metrics. These results invite a renewed study of major pyroCb events in the satellite‐data era (i.e., since 1979) and a new baseline with which to assess more recent and likely future pyroCb events in the climate system. Key Points: The height and lifetime of a 2017 stratospheric pyroCb smoke plume exceeded prior observations post 1979 despite some ordinary source terms Direct pyroCb injection above the tropopause is confirmed by radar data, and MISR stereographic plume‐height the morning after the event Several previous, published pyroCb events were characterized by diabatic lofting of smoke from an initial residence in the stratosphere